Response of Mycorrhizal ’Touriga Nacional‘ Variety Grapevines to High Temperatures Measured by Calorespirometry and Near-Infrared Spectroscopy - Nogales, A.; Ribeiro, H.; Nogales-Bueno, J.; Hansen, L.D.; Gonçalves, E.F.; Coito, J.L.; Rato, A.E.; Peixe, A.; Viegas, W.; Cardoso, Hélia (MDPI, 2020)
Heat stress negatively affects several physiological and biochemical processes in grapevine plants. In this work, two new methods, calorespirometry, which has been used to determine temperature adaptation in plants, and near-infrared (NIR) spectroscopy, which has been used to determine several grapevine-related traits and to discriminate among varieties, were tested to evaluate grapevine response to high temperatures. ‘Touriga Nacional’ variety grapevines, inoculated or not with Rhizoglomus irregulare or Funneliformis mosseae, were used in this study. Calorespirometric parameters and NIR spectra, as well as other parameters commonly used to assess heat injury in plants, were measured before and after high temperature exposure. Growth rate and substrate carbon conversion efficiency, calculated from calorespirometric measurements, and stomatal conductance, were the most sensitive parameters for discriminating among high temperature responses of control and inoculated grapevines. The results revealed that, although this vine variety can adapt its physiology to temperatures up to 40 °C, inoculation with R. irregulare could additionally help to sustain its growth, especially after heat shocks. Therefore, the combination of calorespirometry together with gas exchange measurements is a promising strategy for screening grapevine heat tolerance under controlled conditions and has high potential to be implemented in initial phases of plant breeding programs.
Keywords: Vitis vinifera L; stress tolerance; arbuscular mycorrhizal fungi; chlorophyll fluorescence; membrane permeability; relative chlorophyll content; stomatal conductance